PENGARUH PENERAPAN KOMPONEN GUIDED READING TERHADAP KETERAMPILAN MEMBACA PUISI DI SEKOLAH DASAR - Wahyuni, Anjelina; Halidjah, Siti; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to analyze the influence of the application of whole language approach of guided reading component of poetry reading skill of grade V students of State Elementary School 14 Pontianak Selatan. The research method used is the experimental method, while the research form used is the sample population. Data collection techniques used in this study is a measurement technique with the scoring of students' poetry reading skills. Based on result of data analysis from mean value of result of pre-test 50 and average post-test 68,517. The result of t test obtained t table on the significant level α = 5% is 2.086. Because t count (16,405) > t table (2,042), then hypothesis testing of post-test data is accepted if t count > t table then alternative hypothesis (Ha) is accepted. From the calculation of effect size (ES), obtained by 0.143 Learning by applying the whole language approach of guided reading component gives a big influence to the poetry reading skill of grade V students of State Elementary School 14 Pontianak Soulth. Keywords: Influence, Whole Language Approach Guided Reading Components, Poetry Reading Skills